Biotransformation of 21-O-acetyl-deoxycorticosterone by cell suspension cultures of Digitalis lanata (strain W.1.4) - Maia de Pádua, Rodrigo; Meitinger, Nadine; de Souza Filho, José Dias; Waibel, Reiner; Gmeiner, Peter; Braga, Fernão C.; Kreis, Wolfgang (Steroids, 2012)
Cell cultures of Digitalis species are known to accept exogenous substrates for biotransformation reactions. We here report the biotransformation of 21-O-acetyl-deoxycorticosterone (1) by cell suspension cultures of Digitalis lanata strain W.1.4. Nine derivatives of 1 were obtained and their chemical structures determined by spectroscopic methods. 2β-Hydroxylation and C-21-glucosylation of the steroidal nucleus were described for the first time in suspension-cultured plant cells. Steroid 5α- and 5β-reduction products were also observed. Among the compounds isolated and structures elucidated were 2β,3β,21-trihydroxy-4-pregnen-20-one, 2β,3α,21-trihydroxy-4-pregnen-20-one and 3β,21-dihydroxy- 5α-pregnan-20-one-3β-O-β-glucoside. © 2012 Elsevier Inc. All rights reserved.